Optical and Electrical Transport Properties of the ZnO:CdO Composite Film - Mussabekova, A.K.; Tussupbekova, A.K.; Aimukhanov, A.K. (Karagandy University of the name of acad. E.A. Buketov, 2022)
In this work, zinc oxide films and composite ZnO:CdO films with cadmium oxide concentrations of 3 , 5 , 7 , 10 , and 12 were obtained by spin-coating on FTO. The films were annealed in the atmosphere under the same temperature conditions of 450°C. The morphology of ZnO:CdO composite films was studied by the SEM method and an electron-dispersion analysis of the concentration of the studied substance was carried out. The influence of the surface morphology of the composite film with an increase in the CdO concentration from 3 to 12 on the optical and electrotransport properties of the ZnO:CdO composite film was studied. The optical absorption spectra of composite films of zinc oxide and cadmium were measured. A Tauc plot is presented to determine the band gap of a ZnO:CdO composite film. It has been established that an increase in the CdO concentration on the ZnO surface leads to a decrease in the optical band gap. The observed decrease in the optical band gap of the film with increasing CdO is due to the small band gap of CdO. The method of impedance spectroscopy was used to study the main electrophysical characteristics, in particular, the dynamics of charge carrier transfer in nanocomposite films based on ZnO:CdO. It has been established that the CdO layer on the ZnO surface contributes to a decrease in the resistance value of the composite film Rw, an increase in the charge recombination resistance parameter Rrec at the interface, and an increase in the efficiency of electron injection.
ZnO:CdO композитті қабықшаның оптикалық және электротасымалдау қасиеттері
Оптические и электротранспортные свойства композитной пленки ZnO:CdO
Keywords: ZnO; CdO; composite; morphology; electron transport layer; absorption; structural layer; impedance spectroscopy